Regulating liquidity risk in mutual funds - Dominic Cucic (Danmarks Nationalbank, 2021)
I analyze the effects of liquidity risk regulation in a model of investors, mutual funds, and the underlying asset market. Investor redemptions lead mutual funds to sell assets, which may result in fire sales if market liquidity, driven by the anticipation of fire sales, is scarce. Mutual funds optimally choose to pass fire sales of their assets on to investors. Pecuniary externalities make liquidity supply to the underlying asset market inefficiently low. Regulatory policies, liquidity requirements for mutual funds, and redemption gates have adverse effects on liquidity provision to the asset market and may increase the incidence of fire sales.
Keywords: D62; G11; G23; G38; 330; Financial stability; Financial regulation; Financial institutions